(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Discipline of students in the teaching and learning process is very important to support the suSDN 01 Iwul, SDN 02 Iwul, SDN 03 Iwuless of the teaching and learning process in the classroom during the COVID-19 pandemic. However, many students lack discipline when participating in the teaching and learning process during the COVID-19 pandemic, such as being late for a Zoom class, turning off the camera unilaterally for various reasons, and turning off the sound when asked to participate for technical reasons. This study aims to find out a clear picture of the teacher's strategy in disciplining student learning online during the Covid-19 pandemic at SDN 01 Iwul, SDN 02 Iwul, and SDN 03 Iwul. The approach in this study is a qualitative approach, the method used is a descriptive method. Sources of data used in this study is primary data. Primary data were obtained from the answers to interviews conducted with key informants who were designated as research samples. The result of this study is that student discipline in the implementation of online learning during the Covid-19 pandemic at SDN 01 Iwul, SDN 02 Iwul, and SDN 03 Iwul is quite good. Teachers teach based on lesson plans and syllabus and teach with mixed methods (blended learning) using whats up group applications, google class rooms, and google meet in learning. The teacher's strategy in disciplining student learning online is by making learning contracts, providing understanding material about discipline with the narrative method. And being an example by always being on time, besides that, the teacher always gives assignments to get students to be disciplined in learning. The obstacles that oSDN 01 Iwul, SDN 02 Iwul, SDN 03 Iwulur after the student discipline strategy is implemented are that there are still students who do not do assignments on time, student participation in conveying arguments or opinions is still low so that learning runs monotonously. In addition, students often commit plagiarism in completing their assignments. The efforts made are by always advising and providing an understanding of the importance of discipline and providing good examples and examples to students. Create groups, so that students are more active in learning because they have to present and discuss. The next step, if three times the student is reprimanded, the student is not also present in the online class and does not collect assignments, then the teacher asks the homeroom teacher and BK teacher for help to reprimand the student.